Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1468-2982.2000.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Excitability in Patients with Migraine with Aura and Hemiplegic Migraine

Abstract: We studied the excitability of the motor cortex using transcranial magnetic stimulation (TMS) in 12 patients with migraine with aura (MA) and nine patients with familial hemiplegic migraine (FHM). Motor thresholds at rest, the duration of the cortical and peripheral silent period and intracortical inhibition and facilitation using paired-pulse TMS at intervals of 2 to 15 ms were measured with patients free of attacks for at least 48 h. In contrast to previous reports we could not find any significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
50
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 35 publications
11
50
2
4
Order By: Relevance
“…Similarly, no interhemispheric difference between these parameters was noted. Our results support the studies 10,16 indicating that there is no hyperexcitability of motor cortex in migraine patients during interictal period.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, no interhemispheric difference between these parameters was noted. Our results support the studies 10,16 indicating that there is no hyperexcitability of motor cortex in migraine patients during interictal period.…”
Section: Discussionsupporting
confidence: 92%
“…Another two studies, however, showed no interictal changes of excitability of the motor cortex in migraine. 10,16 In our study performed during the interictal period, we did not find any significant difference in either MwA and MwoA patients compared with controls, in respect to the motor threshold, cortical MEP latencies and amplitudes, MEPmax/CMAPmax ratio and CMCT. Similarly, no interhemispheric difference between these parameters was noted.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Die CSSP und die Paarstimulation mit verschiedenen ISI als Parameter der Intaktheit inhibitorischer intrakortikaler Mechanismen zeigten nur insignifikante Abweichungen von der gesunden Kontrollgruppe [118,133,135] [136]. Modulationen über multisynaptische Verschaltungen in der Formatio retikularis und suprasegmentale Einflüsse unter Einschluss serotonerger Systeme wurden diskutiert [137,138].…”
unclassified